Patch Test Analysis of Channa Striata Extract Biopolymer - Dalimunthe, Dina A; Lubis, Flora Marita; Hazlianda, Cut Putri; Sinaga, Riana Miranda; Dhillon, Jesryn; Hutagalung, Patricia; Berlian, Guntur (Journal of Society Medicine, 2025)
Introduction: Wound healing involves complex interactions between cells and mediators that occur immediately after the wound occurs and depends on nutritional factors and wound closure. Snakehead murrel fish (Channa striata) extract has been extensively researched to speed up the wound healing process because of its high amino acid content. Patch tests were carried out to assess the allergen potential of the Channa striata extract biopolymer in the form of wound dressings. Methods: Experimental study of 40 subjects who had admit patch test with various consentration of Channa striata extract biopolymer. The patch test materials divided of 5 grups. They were aquadest solution, Eucheuma cottonii biopolymer, Channa striata extract biopolymer concentrations of 5.4 g/mL, 10.8 g/mL, and 21.6 g/mL. All subjects had been assessed for skin reactions that occured after 48 hours, 72 hours, and 96 hours. Results: A total of 40 subjects met the inclusion criteria and completed informed consent.  There was minimum allergen reaction (+) in slight subject in all grups except aquadest grup after 48 hours. The allergic reaction dissolve in 72 and 96 hours. An irritant reaction (IR) occurred in among all grups but indicated to the  hypafix plaster. Conclusion: Patch test containing biopolymer Channa striata extract showed a minimal allergic reaction